Comparison the levels of achievements compared to students of the first year in the University of Technology who had Physical Education lesson in their curriculum - Najdat, Esam; Akram, Luma (Journal of Physical Education, 2009)
The research tackles the positive effect of physical education lesson that has been removed from the curriculum of Technology University and the comparison with academic achievements of students. The subjects were first year students of the Technology University of the Academic Year 1987 - 1988 who had physical education lesson in their curriculum and first year students of the Technology University of the Academic Year 1993 - 1994 who did not have physical education lesson in their curriculum. The researcher concluded that students who had physical education lesson in their curriculum had higher levels of achievements compared to students with no physical education lesson in their curriculum